From Nomads to Nomadpolises: Urbanism in Kazakhstan between Heritage and AI - Nurdubaeva, A.R.; Omarova, A.T.; Dauletbayeva, L.M.; Shugaipova, Zh.G. (Karagandy University of the name of acad. E.A. Buketov, 2025)
Contemporary urbanism faces the challenge of balancing technological progress and cultural sustainability. For Kazakhstan, with its nomadic heritage and unfinished urbanization, is the concept of neo-nomadism, synthesizing mobility, digital technologies and environmental principles, relevant? The potential for adapting nomadic traditions in urban design, global trends and local characteristics, historical trends in urbanism related to the understanding of mobility as a key element of urban planning were explored. It seems that contemporary urbanism is moving towards a synthesis of adaptability, inclusiveness and sustainability, but retains the legacy of modernist paradigms, and the cultural and historical context suggests the integration of traditional elements into the modern urban planning model of Kazakhstan.
Keywords: spatial inequality; socio-cultural approaches; digital platforms; adaptive urbanism; nomadic heritage; technological progress; cultural sustainability; urbanism of Kazakhstan; neonomadism